LABOR RETENTION STRATEGY IN UMKM LEADING SECTOR IN SUNGAI PENUH CITY: Deky Hamdani, Indra Budaya - Hamdani, Deky (Qawwam : The Leader's Writing, 2024)
This study examines workforce retention strategies in Micro, Small and Medium Enterprises (MSMEs) in the leading sector in Sungai Penuh City. With high employee turnover posing a significant challenge to the sustainability of MSMEs in the area, this study aims to identify the relationship between workforce retention strategies and MSME performance. Through a quantitative approach based on secondary data, the study used sentiment analysis and Structural Equation Modeling (SEM) to analyze the factors that influence employee retention and its impact on productivity. The results show that competitive compensation, career development, and a conducive work environment are positively correlated with retention rates and improved MSME performance. These findings provide a foundation for the development of effective workforce retention strategies for MSMEs in the leading sector in Sungai Penuh City.